IMPORTANCE OF UZBEK FOLK INSTRUMENTS - Abdukadirova Donokhon Abdulhakim qizi; Hasanova Mamurahon Ahmadjon qizi; Rakhmonova Dilshoda Tavakkal qizi; Kholikova Nilufar Anvarjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides information about the instruments of Uzbek folk music. The role of Uzbek national musical instruments in people’s lives and their duties are highlighted. We can see once again that it is the duty of each of us to promote the importance of our national musical instruments in the lives of young people, to preserve their place and originality.